We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
122
1
avatar

Solve the quadratic equation by completing the square.

2x^2+2=3x

Express your answer in simplified form.

 Jan 19, 2019
 #1
avatar+27891 
+3

"Solve the quadratic equation by completing the square.

2x^2+2=3x"

 

Divide through by 2

x^2 + 1 = 3x/2

 

Rearrange

x^2 - 3x/2 = -1

 

Add  (1/2*3/2)^2 to both sides:

x^2 - 3x/2 + (1/2*3/2)^2 = (1/2*3/2)^2 - 1  or  x^2 - 3x/2 +9/16 = -7/16

 

Equation can now be written as (x - 3/4)^2 = -7/16

 

Hence   x = 3/4 ± √(-7/16)    or  x = (3 ± i√7)/4

.

 Jan 19, 2019

7 Online Users

avatar